Isolation and Identification of Cellulolytic and Xylanolytic Bacteria from Huancarhuaz Hot Spring, Peru - Tamariz-Angeles, Carmen (2014)
Aims: To isolate and characterize lignocellulase producing thermophilic bacteria from a Peruvian hot spring. Study Design: Combined sediment and water samples from the hot spring were subjected to direct plating, in situ baiting and ex situ enrichment. Endoglucanase and xylanase producing bacterial colonies were isolated and characterized. Place and Duration of Study: Samples were taken from the Huancarhuaz hot spring, Peru (8º56’31.86”S, 77º47’00.53”W) in August 2010 and processed during 2011-2013. Methodology: Samples were subjected to three isolation methods and bacterial colonies with different color, size and appearance, were isolated, purified by streaking several times and conserved in Tryptic Soy Agar slants at 4ºC. The agar staining method was used to isolate enzyme-producing strains which were then identified by 16S rRNA sequencing and further studied for endoglucanase and xylanase production. Results: From 19 bacterial isolates only eight were selected for further study as they showed clearing activities on both carboxymethyl cellulose and xylan agar plates. By using 16S rRNA gene phylogenetic analysis, seven isolates were identified as Bacillus licheniformis and one as Cohnella laeviribosi which was the best xylanase and endoglucanase producer. Maximum endoglucanase activity produced by C. laeviribosi EHB4 was obtained at pH 6.0 and at 60ºC and only 50% of its activity was lost at 90ºC for 1h indicating that this enzyme is particularly thermostable. Conclusion: This is the first report on the production of endoglucanase by C. laeviribosi. These findings indicate that Peruvian hot springs are good sources of thermophilic cellulase-producing bacteria and that C. laeviribosi EHB4 may contribute to the development of biomass bioconversion processes.